Falling and heaviness: Heaviness judgment for a visual object which users lift up is influenced by the presentation of the object's falling or staying still - Ujitoko, Yusuke; Kaneko, Seitaro; Yokosaka, Takumi; Kawabe, Takahiro (Frontiers in Psychology, 2023)
When lifting and subsequently releasing a visual object on a screen using a computer mouse, users tend to judge the object to be heavier when the motion speed of the object during lifting is smaller. However, it was unclear how the presentation of an object falling after its release influenced the judgment of heaviness. Users generally believe mistakenly that heavier objects fall faster. Based on the previous report of this misbelief, we briefly explored how the falling speed of a visual object after release by a user influenced the judgment of heaviness. The falling speed of the object was systematically modulated by changing gravity in the simulation of the natural falling of the object. Participants judged the object's heaviness after they lifted and subsequently released it. As a result, the participants judged the object to be lighter when the falling speed was zero. However, no significant differences were observed among the conditions with a falling speed greater than zero. It is suggested that for the judgment of heaviness, a vital aspect in the presentation of a falling object after releasing is whether the object falls or not.